Participação de mulheres na gestão esportiva: uma revisão sistemática - Belan, Bruna Bressan [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
During the last decades of the XX century occurred several demographic, cultural and social changes that directly affected the inclusion of women in the labor market. However many of them have found and still find barriers to work in various fields of endeavor and in the case of this study, the sports management. The purpose of this study was to assess through a systematic review, the participation of women in sports management, listing the main characteristics, challenges and difficulties. The research consisted of a systematic review of studies that discuss the thematic related to the participation of women in sport management in Brazil, including the Google Scholar database. The key words used and that generated proceeds were woman, sports management and women in sports administration. In the discussion and results has been possible to list the insert forms in a management position, the main ones being: by invitation, conduction or family relationship. The arguments about the limited participation of women in sports management and their encountered barriers are justified because there is a male domain and prejudice, resulting often the career waiver for these women. The profile of the sporting managers has found a predominance of men aged between 30-49 years old. For unavailability of articles, the present study was restricted to use only one database. In short, there is a lacuna in studies on women's participation in the administration or sporting management, with a prevalence of literature review articles. To expand overview on this issue would be important to carry out quantitative studies. It was concluded that the difficulty of women entering in sports management still seems to be a current problem and can only be minimized from a greater attention from the scientific community. It is suggested to carry out further studies that address more deeply the reasons for this disparity, aimed at proposing specific changes to the...

Nas últimas décadas do século XX, ocorreram diversas alterações demográficas, culturais e sociais que afetou diretamente a inserção da mulher no mercado de trabalho. Porém muitas delas encontraram e ainda encontram barreiras para atuar em vários campos de atuação e no caso desse estudo, o da gestão esportiva. O objetivo principal deste estudo foi avaliar, por meio de uma revisão sistemática, a participação das mulheres na gestão esportiva, elencando as principais características, desafios e dificuldades. O estudo foi constituído de uma revisão sistemática de estudos que abordam a temática relacionada com a participação das mulheres na gestão do esporte no Brasil, abrangendo a base de dados Google Acadêmico. As palavras chaves utilizadas e que geraram um resultado foram: mulher, gestão esportiva e mulher na administração esportiva. Como discussão e resultados foi possível elencar as formas de inserção no cargo de gestão, sendo as principais, por convite, condução ou laços familiares; os argumentos sobre a restrita participação da mulher na gestão esportiva e suas barreiras encontradas, onde são justificadas por existir um domínio masculino e preconceito, acarretando, muitas vezes a desistência da carreira por essas mulheres. O perfil do gestor esportivo encontrado tem predominância de homens com faixa etária entre 30 a 49. Por indisponibilidade de artigos, o presente estudo ficou restrito ao utilizar apenas uma base de dados. Em suma, existe uma lacuna em estudos sobre a participação das mulheres na administração ou gestão esportiva, com uma prevalência de artigos de revisão de literatura. Para ampliar a visão sobre esse tema seria importante à realização de estudos quantitativos. Foi possível concluir que a dificuldade da inserção da mulher na gestão esportiva parece ainda ser um problema atual e que somente poderá ser minimizado a partir de uma maior atenção...
Keywords: Esportes - Administração; Mulheres e esportes; Mulheres nas profissões; Pesquisa bibliografica